EFEK AKTIFITAS FISIK TERHADAP TEKANAN DARAH DAN GLUKOSA DARAH PADA LANSIA - Haqiqi, Rahmat Hidayat; Yuliastrid, Dita; Kumaat, Noortje Anita; Sulistyarto, Soni (Universitas Hamzanwadi, 2025)
The study was designed to assess whether there is a relationship between physical activity and blood pressure and blood glucose in the elderly at Posyandu Bangsalsari. This research is a type of non-experimental research with a cross-sectional study design and uses a descriptive quantitative approach based on correlation. The population in this study were elderly people who were in the Bansalsari Posyandu Lansia with a total of 20 elderly people aged 60 to 75 years, 5 men and 15 women. Data analysis techniques include descriptive analysis, namely numerical data that can be categorized and categorical will be presented frequency distribution using percentage values. The result is that the average blood pressure is in the normal category with mean systolic and diastolic values of 137.75 mmHg and 85.8 mmHg respectively. While the average blood glucose was in the moderate category at 156 mg/dl. Physical activity was identified to have a significant relationship with blood pressure, both systolic and diastolic and blood glucose (sig. < 0.05). The negative correlation with r values = - 0.594, -0.592, - 0.663 implies that the higher the physical activity, the lower the blood pressure and blood glucose. Therefore, it is recommended that the elderly of Posyandu Bangsalsari have regularity in physical activity that can help stabilize and reduce blood pressure and blood glucose.